2008
DOI: 10.1007/s11274-008-9714-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of several factors on soluble lipase-mediated biodiesel preparation in the biphasic aqueous-oil systems

Abstract: Biodiesel is increasingly perceived as an important component of solutions to the important current issues of fossil fuel shortages and environmental pollution. Utilization of soluble lipase offers an alternative approach to lipase-catalyzed biodiesel production using immobilized enzyme or whole-cell catalysis. Soluble lipase NS81020, produced by submerged fermentation of genetically modified Aspergillus oryzae microorganism, was first proposed here as the catalyst of biodiesel preparation with oleic acid in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 25 publications
2
30
1
Order By: Relevance
“…6 and the simulated parameters for rate constant VEs and equilibrium constant K I are 90.7755 L/(mol.min) and 3.9087 respectively. Compared with other equilibrium constants shown in Table 2, the inhibitory constant of methanol are relative higher, which confirmed that the inhibitory effect of methanol existed in the reaction and this was consistent with many literatures [26][27][28].…”
Section: Free Lipase-catalyzed Esterification Of Oleic Acid and Methanolsupporting
confidence: 89%
See 1 more Smart Citation
“…6 and the simulated parameters for rate constant VEs and equilibrium constant K I are 90.7755 L/(mol.min) and 3.9087 respectively. Compared with other equilibrium constants shown in Table 2, the inhibitory constant of methanol are relative higher, which confirmed that the inhibitory effect of methanol existed in the reaction and this was consistent with many literatures [26][27][28].…”
Section: Free Lipase-catalyzed Esterification Of Oleic Acid and Methanolsupporting
confidence: 89%
“…4 was used to describe the esterification process of FFA. Meanwhile, it's also very important to incorporate the effect of methanol into the model since the presence of methanol in the reaction system may involve in the inactivation of enzyme [26,27]. Thereby, the inhibitory effect of methanol was also considered.…”
Section: Determination Of Kinetic Constantsmentioning
confidence: 99%
“…The result proved that alkaline pH was preferable for transesterification reaction. The same conclusion was also reported by Chen and Zhao separately [24,25]. The speculation was that hydroxyl ion depressed hydrolysis of FAMEs resulting in higher biodiesel conversion [24].…”
Section: Discussionsupporting
confidence: 74%
“…However, although free enzymes are significantly cheaper than immobilized lipases, in many cases they have poor operational stability and can only be used once, as they are inactivated [14]. There are a few reports available on soluble lipase-catalyzed biodiesel production [24,25], including the methanolysis of low cost crude soybean oil using Callera Trans L (lipase from T. lanuginosus) [26]. In order to prevent the addition of water to the reaction medium, the solution containing the free lipase can be freeze-dried.…”
Section: Free Lipasesmentioning
confidence: 99%